Effects of a Brief Strange Loop Task on Immediate Word Length Comparison: A Mindfulness Study on Non-striving - Kee, Ying Hwa; Aye, Khin Maung; Ferozd, Raisyad; Li, Chunxiao (Frontiers in Psychology, 2019)
Non-striving is an important aspect of mindfulness practice, but it has not been sufficiently researched. This study examine whether a strange loop based task — Infinite Water Scooping Task — performed for ten minutes, has an effect on non-striving behaviour and performance in a subsequent word length comparison task. Results showed that performance (number of correct trials) did not differ significantly between the two groups, though the experimental group tended to perform worse. However, participants in the experimental group took a significantly shorter time to respond to the word length comparison task than those in the control group. It is inferred that shorter time taken reflects response without investing much effort to count with care, i.e. non-striving. The present study demonstrates that the brief strange loop task implemented in this study elicited non-striving behaviour compared to the effects of the control task and adds to the understanding of non-striving in the context of mindfulness. The Infinite Water Scooping Task may be useful for illustrating and teaching non-striving within mindfulness practice.